The psychosocial quality of work determines whether employment has benefits for mental health: results from a longitudinal national household panel survey. Issue 11 (14th March 2011) - Butterworth, P; Leach, L S; Strazdins, L; Olesen, S C; Rodgers, B; Broom, D H
Abstract : Objectives: Although employment is associated with health benefits over unemployment, the psychosocial characteristics of work also influence health. We used longitudinal data to investigate whether the benefits of having a job depend on its psychosocial quality (levels of control, demands and complexity, job insecurity, and unfair pay), and whether poor quality jobs are associated with better mental health than unemployment. Method: Analysis of seven waves of data from 7, 155 respondents of working age (44, 019 observations) from a national household panel survey. Longitudinal regression models evaluated the concurrent and prospective association between employment circumstances (unemployment and employment in jobs varying in psychosocial job quality) and mental health, assessed by the MHI-5. Results: Overall, unemployed respondents had poorer mental health than those who were employed. However the mental health of those who were unemployed was comparable or superior to those in jobs of the poorest psychosocial quality. This pattern was evident in prospective models: those in the poorest quality jobs showed greater decline in mental health than those who were unemployed (B = 3.03, p<0.05). The health benefits of becoming employed were dependent on the quality of the job. Moving from unemployment into a high quality job led to improved mental health (mean change score of +3.3), however the transition from unemployment to a poor quality job was more detrimental to mental health than remaining unemployed (−5.6 vs −1.0). Conclusions: Work of poor psychosocial quality does not bestow the same mental health benefits as employment in jobs with high psychosocial quality.